The impact of organizational resilience on hotel performance during pandemic COVID-19 - Mohammad Hamsal; Sri Bramantoro Abdinagoro; Arif Zulkarnain; Dino Gustaf Leonandri; Mohammad Ichsan (Global Business & Finance Review (GBFR), 2022)
Purpose: This study aims to examine the impact of dynamic capabilities and organizational resilience on firm performance driven by environmental turbulence of the hotel industry in Indonesia during the pandemic COVID-19. Design/methodology/approach: Herein, an integrated conceptual framework is developed and then tested using survey data from a cross-section of 194 hotels using structural equation modelling. Findings: The result of this research reveals that environmental turbulence significantly affects dynamic capabilities empirically. In other words, the dynamic capabilities affect organizational resilience, however, there is no significant effect from organizational resilience to hotel performance. This shows an indication of survival mode in the hotel industry in Indonesia. Research limitations/implications: This study extends theoretically the concept of organizational resilience in the context of environmental turbulence especially during pandemic COVID-19. Practical implication of this study justifies that during such crisis, it is imperative for the organizations to focus on survival rather than financial performance. Originality/value: This study introduces the antecedents of organizational resilience, namely the dynamic capabilities and environmental turbulence in the context of pandemic COVID-19. It also advances the knowledge on how the hotel industry can be managed during that period.
Keywords: 650; Environmental turbulence; Dynamic capabilities; Organizational resilience and Firm performance; Pandemic; COVID-19; Hotel